Fighter squadron [videorecording (DVD)] - Miller, Seton I.; Walsh, Raoul, 1887-1980; O'Brien, Edmond, 1915-1985; Rodney, John; D'Andrea, Tom, 1909-1998; Hull, Henry, 1890-1977; Holden, James; Hudson, Rock, 1925-1985 (Archive collection., 2010)
U.S. airman Ed Hardin pilots a damaged P-47 Thunderbolt toward a perilous but successful belly flop landing at his fighter-group base in the English countryside. The battered aircraft may never wing into the skies again. Hardin will. 'Notify the taxpayer to get me another one, ' he quips. Hardin tempers his flyboy recklessness when the men of the squadron are entrusted to his leadership.